CORPORATE ETHICAL VALUES AND ORGANIZATIONAL JUSTICE AS DETERMINANTS OF WORKPLACE STRESS, EMPLOYEES’ PSYCHOLOGICAL AND SOCIAL WELL-BEING - Babalola, Dr Segun; Ogunyemi, Ajibola (African Journal of Behavioural and Scale Development Research, 2022)
The present study was carried out to examine corporate ethical values and organizational justice as predictors of workplace stress and psychological and social well-being in a sample of 120 employees of eight commercial banks in Ogun East senatorial district, Nigeria. Multivariate Analysis of Variance and Multiple Regression Analysis were employed. Results revealed among others, the significant influence of corporate ethical values and organizational justice on the combination of workplace stress, and employees’ psychological and social well-being (Wilk’s Lambda = 23.991, p < .05, partial η2 = .561) and a significant prediction of workplace stress (F = 125.406, p < .05). Corporate ethical values and organizational justice were significant independent predictors of psychological and social well-being.